SMAD4 loss limits the vulnerability of pancreatic cancer cells to complex I inhibition via promotion of mitophagy - Ezrova, Zuzana; Nahacka, Zuzana; Stursa, Jan; Werner, Lukas; Vlcak, Erik; Kralova Viziova, Petra; Berridge, Michael V; Sedlacek, Radislav; Zobalova, Renata; Rohlena, Jakub; Boukalova, Stepana; Neuzil, Jiri (Oncogene, 2021)
Pancreatic cancer is one of the deadliest forms of cancer, which is attributed to lack of effective treatment options and drug resistance. Mitochondrial inhibitors have emerged as a promising class of anticancer drugs, and several inhibitors of the electron transport chain (ETC) are being clinically evaluated. We hypothesized that resistance to ETC inhibitors from the biguanide class could be induced by inactivation of SMAD4, an important tumor suppressor involved in transforming growth factor β (TGFβ) signaling, and associated with altered mitochondrial activity. Here we show that, paradoxically, both TGFβ-treatment and the loss of SMAD4, a downstream member of TGFβ signaling cascade, induce resistance to biguanides, decrease mitochondrial respiration, and fragment the mitochondrial network. Mechanistically, the resistance of SMAD4-deficient cells is mediated by increased mitophagic flux driven by MAPK/ERK signaling, whereas TGFβ-induced resistance is autophagy-independent and linked to epithelial-to-mesenchymal transition (EMT). Interestingly, mitochondria-targeted tamoxifen, a complex I inhibitor under clinical trial, overcomes resistance mediated by SMAD4-deficiency or TGFβ signaling. Our data point to differential mechanisms underlying the resistance to treatment in PDAC arising from TGFβ signaling and SMAD4 loss, respectively. The findings will help the development of mitochondria-targeted therapy for pancreatic cancer patients with SMAD4 as a plausible predictive marker.
Keywords: Pancreatic Neoplasms; Mitophagy; signální transdukce; protein Smad4; Smad4 Protein; lidé; mitofagie; Humans; nádory slinivky břišní; Signal Transduction